Client organizations and the management of professional agency work: The case of English health and social care. Issue 1 (6th September 2018) - Kirkpatrick, Ian; Hoque, Kim; Lonsdale, Chris
Abstract : A growing reliance on agency workers can lead to significant risks for client organizations, especially in core organizational roles. It has been suggested while these risk can be mitigated through investments in human resource management (HRM) directed at agency workers, in reality these will be hard to implement. This article draws upon Lepak and Snell's (1999) HR architecture model and uses a comparative case study method to explore this issue, focusing on agency working in core nursing and qualified social worker roles. The findings illustrate how client organizations can become more involved in the management of agency workers than has previously been acknowledged. Our analysis also identifies the conditions that shape this client‐side involvement, including the nature of agency worker contracts, the role of temporary work agencies, competing organizational cost‐control priorities, and perceptions of the regulatory context. These conditions are brought together in a general model for understanding the largely neglected role that client organizations play in the HR management of agency workers.